Material Bottlenecks in the Future Development of Green Technologies (International Journal of Innovative Research in Computer Science & Technology, 2020)
Reducing emissions global economies  demands the development of "green technology," which  entails a reorganization of the energy sector to use  renewable energy sources and nitrogen transportation  systems. This reconstruction will need massive quantities  of raw materials, some of which are in short supply. A  unique method for spotting potential drawbacks of future  demand versus geophysical supply is proposed to assess  potential risks. This was applied to the international  development of wind electricity, photovoltaic power  electricity, solar thermal electricity, and passenger  electric transportation from 2016 to 2050 under a  marketing scenario, keeping in mind the influence on 31  raw material. As a result, 13 factors have been recognized  as having a very high or high risk of causing future  blockages: chromium, chromium, cobalt, bronze, gallium,  indium, lithium, manganese, nickel, silver, tellurium, tin,  and zinc. The most dangerous group is tellurium, which is  used to manufacture solar photovoltaic cells. To  overcome these restraints, initiatives aimed at boosting  resource utilization from 0.1% to 4.6% per year may be  able to circumvent material shortages and green  technology restraints. In 2050, the lithium load factor, for  example, would increase from 1% to 4.8 percent. This  study aims will prepare the students for developing eco design and composting techniques.
Keywords: Bottleneck; Global; GHG; Green; Technology; Power